2022
DOI: 10.24996/ijs.2022.63.10.10
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the prevalence and antibiotic susceptibility patterns of S. aureus bacteria isolated from Iraqi women with vaginosis

Abstract: Bacterial vaginosis (BV) is a common infection that occurs when the number of lactobacillus spp. bacteria (vaginal flora) decreases in the vaginal canal. The study aimed to determine the prevalence of Staphylococcus aureus within vaginosis in order to emphasize the importance of early detection and treatment. Totally, 90 vaginal swabs were collected using speculum and swabbing. The vaginal swabs were subjected to standard microbiological testing, which included microscopy, cultures (Blood agar and Mannitol sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
(13 reference statements)
0
0
1
Order By: Relevance
“…Conclusions from the current study found that the isolates were resistant to doxycycline at a rate of (3.1%), which is not comparable to the findings of [26,27], who recorded a resistance rate of doxycycline of 20.6% and 30%, respectively. azithromycin had a resistance rate of 28 (87.5%) of MRSA isolates, which was less low than the results of [28], who published that the resistance rate of MRSA isolates against azithromycin was 92.5%.…”
Section: Thirtycontrasting
confidence: 99%
“…Conclusions from the current study found that the isolates were resistant to doxycycline at a rate of (3.1%), which is not comparable to the findings of [26,27], who recorded a resistance rate of doxycycline of 20.6% and 30%, respectively. azithromycin had a resistance rate of 28 (87.5%) of MRSA isolates, which was less low than the results of [28], who published that the resistance rate of MRSA isolates against azithromycin was 92.5%.…”
Section: Thirtycontrasting
confidence: 99%